1999
DOI: 10.1136/vr.144.16.437
|View full text |Cite
|
Sign up to set email alerts
|

Acute phase proteins in cattle: discrimination between acute and chronic inflammation

Abstract: Acute phase proteins such as serum amyloid A, haptoglobin, and alpha 1-acid glycoprotein have been identified as markers of inflammation in cattle because they are produced by the liver in response to pro-inflammatory cytokines. This study was designed to assess whether they could be used to discriminate between acute and chronic inflammation. Their concentrations were measured in serum samples from 81 cattle in which inflammation was classified by thorough clinical examination, supported by postmortem finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

24
241
2
20

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(299 citation statements)
references
References 25 publications
24
241
2
20
Order By: Relevance
“…Normal concentrations of haptoglobin are reported to be less than 0.35 mg/mL (Horadagoda et al, 1999), but in both age groups and throughout the 28 days post-castration, concentrations were above this. Indeed, even the pre-treatment concentrations were elevated above normal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal concentrations of haptoglobin are reported to be less than 0.35 mg/mL (Horadagoda et al, 1999), but in both age groups and throughout the 28 days post-castration, concentrations were above this. Indeed, even the pre-treatment concentrations were elevated above normal.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, even the pre-treatment concentrations were elevated above normal. Although haptoglobin is reported to be a sensitive acute-phase protein in cattle indicative of systemic inflammation (Horadagoda et al, 1999), it has been found to be elevated by social and psychological stressors in some species,…”
Section: Discussionmentioning
confidence: 99%
“…Serum amyloid A (SAA) is a sensitive APP in cattle [1,8,11,13,24]. SAA has been shown to reflect the severity of mastitis; cows with clinical mastitis had almost 100-fold levels of SAA in serum and milk compared with healthy cows [5].…”
Section: Introductionmentioning
confidence: 99%
“…whose concentrations change in response to injury, infection or inflammation as part of the systemic response. In cattle, haptoglobin has been found to be a useful marker of inflammation (Horadagoda et al, 1999). Therefore, we chose haptoglobin to ascertain if calves fed the experimental diet could suffer injuries or bacterial infections associated with low ruminal pH, like liver damage or lipopolysaccharides reaching the bloodstream, but no livers were removed because no abscesses were visible.…”
mentioning
confidence: 99%